The Direct and Indirect Losses to Ukraine’s Economy Caused by Hostilities - Samborska Oksana Yu.; Materynska Olha A. (Bìznes Inform)
The article studies the partial or complete destruction of the leading and budget-forming sectors of the country’s economy, damage to world-famous enterprises; losses at the national level of certain sectors of the economy as a result of hostilities on the territory of Ukraine are calculated. Particular attention is paid to the decrease in the country’s population, migration of the able-bodied population, and the loss of total income of family households. The indicator of poverty of the population during the war is determined. The number of Ukrainian citizens who crossed the border in both directions due to the ongoing war has been made public. An assessment of direct losses and destruction, damage to public sector facilities, social facilities and institutions, educational, scientific and health care institutions, and administrative buildings was carried out. The study notes that the destruction of warehouses for storage of agricultural products, disrupted logistical links, the complete loss of access to preferential lending conditions for agricultural producers led to a violation of the terms of the contract for the sale of raw materials and finished products for export, an artificial increase in the cost of goods due to an increase in electricity fees, and the loss of sown areas and territories due to mining by the enemy caused a decrease in the amount of grown raw materials and even the loss of certain industries in the regions. The results of the study show that the ongoing hostilities have caused significant pressure on animal husbandry, even in some cases its complete loss in the occupied territories. The issue of choosing the optimal direction for preserving and using the labor potential of Ukraine, restoring the leading industries and sectors of the economy for the development and recovery of the economy as a whole is raised.